Metal Contents in Water of Ambazari Lake and Nearly Water Sources - Pokale, W.K.; Ghyar, P.B. (Asian Journal of Chemistry, 2010)
Concentration of metals Cd, Fe, AI, Co, Mn, Pb, Zn, Cu, Cr, Na and K in water from Ambazari lake situated at Wadi-Nagpur MIDC area are studied in this paper. To compare the level of these metals, the samples were collected from nearby sources. Also samples were studied from Futala lake which is about 2-3 km away from Ambazari, Nagpur and having no industry in its catchment area.